2010 IEEE Intelligent Vehicles Symposium 2010
DOI: 10.1109/ivs.2010.5548004
|View full text |Cite
|
Sign up to set email alerts
|

Fast prototyping of a Highly Autonomous Cooperative Driving System for public roads

Abstract: This paper presents a framework for a fast prototyping of Advanced Driving Assistance Systems (ADAS). The simulation tool SiVIC is proposed for drastically reducing development time and costs of a vehicle system design. RT Maps ® is used as a platform for easily encapsulating the system component algorithms and for effortlessly transferring them from a simulation environment to a physical vehicle. With these tools a Highly Autonomous Cooperative Driving System (HACS) has been designed. A perception component u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In this study, the simulation stage is carried out according to the diagram block of Fig. 4 and uses two levels of simulation and three different platforms: firstly a Matlab platform is used with a full nonlinear model of the instrumented Peugeot 406 car as in [32], and secondly thanks to the pro-SiVIC 1 platform [26], [25], [40], [24] interconnected with RTMaps platform 2 , we will simulate complex vehicle dynamical modeling [35], environment, infrastructure, and realistic embedded sensors. Moreover pro-SiVIC will provide mechanisms allowing to generate very accurate ground truth for the evaluation and validation stages.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In this study, the simulation stage is carried out according to the diagram block of Fig. 4 and uses two levels of simulation and three different platforms: firstly a Matlab platform is used with a full nonlinear model of the instrumented Peugeot 406 car as in [32], and secondly thanks to the pro-SiVIC 1 platform [26], [25], [40], [24] interconnected with RTMaps platform 2 , we will simulate complex vehicle dynamical modeling [35], environment, infrastructure, and realistic embedded sensors. Moreover pro-SiVIC will provide mechanisms allowing to generate very accurate ground truth for the evaluation and validation stages.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Among the ones that are free, Racer [63] is probably the most known. Other proprietary options include SiVIC [64] and PreScan [65]. A more detailed review of simulators for testing ADAS can be found in [66].…”
Section: Validation and Verificationmentioning
confidence: 99%
“…The simulations are carried out firstly with Matlab using a 10DoF instrumented Peugeot 406 car as in [17], and secondly thanks to the SiVIC 2 simulator [12], [11], [22], [10] interfaced with RTMaps platform 3 .…”
Section: Simulations With Actual Datamentioning
confidence: 99%